Phylogenetic Structure of Plant Communities: Are Polyploids Distantly Related to Co-occurring Diploids? - Gaynor, Michelle L.; Ng, Julienne; Laport, Robert G. (Frontiers in Ecology and Evolution, 2018)
Polyploidy is widely acknowledged to have played an important role in the evolution and diversification of vascular plants. However, the influence of genome duplication on population-level dynamics and its cascading effects at the community level remain unclear. In part, this is due to persistent uncertainties over the extent of polyploid phenotypic variation, and the interactions between polyploids and co-occurring species, and highlights the need to integrate polyploid research at the population and community level. Here, we investigate how community-level patterns of phylogenetic relatedness might influence escape from minority cytotype exclusion, a classic population genetics hypothesis about polyploid establishment, and population-level species interactions. Focusing on two plant families in which polyploidy has evolved multiple times, Brassicaceae and Rosaceae, we build upon the hypothesis that the greater allelic and phenotypic diversity of polyploids allow them to successfully inhabit a different geographic range compared to their diploid progenitor and close relatives. Using a phylogenetic framework, we specifically test (1) whether polyploid species are more distantly related to diploids within the same community than co-occurring diploids are to one another, and (2) if polyploid species tend to exhibit greater ecological success than diploids, using species abundance in communities as an indicator of successful establishment. Overall, our results suggest that the effects of genome duplication on community structure are not clear-cut. We find that polyploid species tend to be more distantly related to co-occurring diploids than diploids are to each other. However, we do not find a consistent pattern of polyploid species being more abundant than diploid species, suggesting polyploids are not uniformly more ecologically successful than diploids. While polyploidy appears to have some important influences on species co-occurrence in Brassicaceae and Rosaceae communities, our study highlights the paucity of available geographically explicit data on intraspecific ploidal variation. The increased use of high-throughput methods to identify ploidal variation, such as flow cytometry and whole genome sequencing, will greatly aid our understanding of how such a widespread, radical genomic mutation influences the evolution of species and those around them.